A Review of Options for Health and Disability Support Purchasing in New Zealand - Nicholas Mays; Kenneth Hand (New Zealand Government, The Treasury, 2000)
The introduction of an internal market into New Zealand's publicly financed health system based on a purchaser-provider separation was highly controversial. From four Regional Health Authorities, the purchasing side of the internal market was subsequently reconfigured into a single national purchasing agency, the Health Funding Authority, in 1997. This Working Paper reviews the original rationale for the separation of purchase from provision, discusses the recent experience of the separation in New Zealand and reviews options for the possible evolution of the purchasing function. The options reviewed include vertical integration (ie, the abolition of the purchaser-provider split). It is argued that there are benefits associated with the separation of purchaser and provider, and that, on balance, it was a good thing, although its application to all services was probably inadvisable. However, no one model of purchaser organisation can fulfil all the requirements described by proponents of system change. Health services' purchasers are inescapably in a weak position vis-à-vis their providers. Whichever model of purchasing/planning services is implemented, purchasers will need to develop a new set of relationships with primary care providers, especially general practitioners, since primary care services are important for the functioning of the remainder of the health system. There are currently few incentives on primary care providers to consider the wider implications of their decisions for the rest of the sector and the delivery of primary care is imperfectly coordinated with other services. This paper is a background paper and does not provide policy advice, nor does it propose any particular course of action. The Treasury has chosen to publish it (or make it available) in order to encourage peer comment with a view to ensuring that it is of good quality. The views expressed in the paper is/are those of the author(s) and do not necessarily reflect the views of the New Zealand Treasury. The Treasury takes no responsibility for any errors or omissions in, or for the correctness of, the information contained in this paper.
Keywords: 330